Influence of cheese making technologies on plasmin and coagulant associated proteolysis - Vélez, María Ayelén (2015)
The aim of this work was to study the influence of different cheese-making technologies applied for three varieties of Argentinean cheeses on the action of coagulant enzyme, plasmin-plasminogen system and proteolysis. For this, Cremoso (soft cheese), Pategrás (semi-hard cheese) and Reggianito (hard cooked cheese) cheeses were analyzed for composition, nitrogen fractions, enzymes activities and elecrophoresis throughout ripening. As for coagulant, no reactivation of the enzyme was registered during ripening. Changes were mainly related to cooking temperature, as decreasing cooking temperature increased coagulant activity, being superior in Cremoso, followed by Pategrás and then by Reggianito cheeses. In regards of plamin/plasminogen system, it was observed greater activity of inactive plasminogen in Reggianito and Cremoso cheeses; while in Pategrás cheese the level was very low probably because plasminogen activation was enhanced during cheese making by the elimination of plasminogen activators inhibitors by curd washing. Indeed, the highest plasmin activity was found in Pategrás cheese, which indicates that curd washing combined with soft thermal treatment of the curd favored plasminogen activation. However, the environment defined by Reggianito cheese matrix was more suitable for maintaining the stability of plasmin activity along ripening. Results were consistent with proteolysis registered in electrophoresis and nitrogen fractions.